‘Fra det sted, han kalder jorden’: Mødet med det nonhumane i Olga Ravns De ansatte - Kraglund, Rikke Andersen (Passage - Tidsskrift for litteratur og kritik, 2019)
Based on a reading of science fiction iconography and topics in Olga Ravn’s De ansatte [The employees] the article discusses how the novel uses a fictionalized framework to reflect upon contemporary social discussions.